Persepsi Nasabah Tentang Ketanggapan, Keramahan, Kehandalan, Komunikasi, dan Mengerti Nasabah terhadap Pelayanan Bagian Prioritas PT. Bank Central Asia Surabaya - Arasy Alimudin; I Putu Artaya (BISMA (Bisnis dan Manajemen), 2018)
Object of this research in one of famous bank in Surabaya which is PT Bank Central Asia, with qualitative research type, cause to know how customer bank perception about service that Bank Central Asia give to customer  which is service a main point of customer satisfaction. Perception that tray to measurement using qualitative approachs: responsiveness, communication, durability, hospitality, and understanding customer has satisfaction ones each other during servicing customer. All populations are 1030 customer, take a sample 40 customer which is customer who has deposit 500million rupias